Structural Strength and Service Life of the Extrusion Forming Die for Agricultural Engine Piston Heads - Yang, L.Q.; Lv, Q.Q.; Zhang, H.M.; Zhu, C H.; Wang, W.Z. (Проблемы прочности, 2018)
Three-tier high-strength prestressed combination concave dies are designed to manifacture highpower corn combine harvester engine piston heads. This design integrates the advantages of traditional casting or hot die forging and warm extrusion. The following key parameters, viz radial dimensions of each mating layer, axial bonding and radial contact interaction, are obtained by theoretical calculation. Nonlinear analysis of the contact interaction was carried out, and the die contact condition was studied at no-load and full-load. Based on the Archard wear theory, thermomechanical bonding was studied in operation of the die. Through numerical simulation of the die wear in each operation cycle, the univariate linear regression equation of the die service life was derived, and the reliability of this equation was verified. The results show that the die contact is both stable and reliable if the radial contact interaction of the inner and outer layers is δ₂= 1.9716 mm and δ₃= 1.3870 mm, respectively. With the nitriding layer thickness of 0.24 mm, the extrusion die service life in the production of piston heads corresponds to 6357 pieces.